Intraoperative measurements of reverse total shoulder arthroplasty contact forces - Kevin W. Farmer; Masaru Higa; Scott A. Banks; Chih-Chiang Chang; Aimee M. Struk; Thomas W. Wright (Journal of Experimental Orthopaedics, 2020)
Abstract Purpose Instability and fractures may result from tensioning errors during reverse total shoulder arthroplasty (RTSA). To help understand tension, we measured intraoperative glenohumeral contact forces (GHCF) during RTSA. Methods Twenty-six patients underwent RTSA, and a strain gauge was attached to a baseplate, along with a trial glenosphere. GHCF were measured in passive neutral, flexion, abduction, scaption, and external rotation (ER). Five patients were excluded due to wire issues. The average age was 70 (range, 54–84), the average height was 169.5 cm (range, 154.9–182.9), and the average weight was 82.7 kg (range, 45.4–129.3). There were 11 females and 10 males, and thirteen 42 mm and 8 38 mm glenospheres. Results The mean GHCF values were 135 N at neutral, 123 N at ER, 165 N in flexion, 110 N in scaption, and 205 N in abduction. The mean force at terminal abduction is significantly greater than at terminal ER and scaption (p < 0.05). Conclusions These findings could help reduce inappropriate tensioning.